Unraveling EFL learners’ perceptions and transformative practices in harnessing artificial intelligence for essay writing: Unleashing the potentials? - Suhandoko (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
This study investigates EFL learners’ perceptions and practices regarding the use of artificial intelligence (AI) in essay writing. The research involved 71 participants enrolled in an essay writing course and utilized a questionnaire as the research instrument. The questionnaire aimed to explore learners’ familiarity with AI, their use of AI-based tools, beliefs about the impact of AI on writing skills, confidence in using AI tools, perceptions of AI’s effect on essay quality, satisfaction with AI tools, and ethical concerns. The findings revealed that while the majority of learners had a reasonable understanding of AI technology, there were variations in their level of familiarity. Grammarly was the most frequently used AI tool, followed by Turnitin and Chat GPT. The frequency of AI tool usage varied among learners. Learners held differing beliefs about the impact of AI tools on their writing skills, with some acknowledging positive improvements and others expressing disagreement. Overall, learners exhibited a moderate level of confidence in using AI tools but voiced concerns about essay quality and ethical considerations. The study emphasizes the need for further exploration, educational initiatives, and ethical considerations to effectively integrate AI into essay writing instruction, taking into account the diverse perspectives and requirements of learners.